Ingestion rates of Artemia nauplii for different larval stages of Macrobrachium rosenbergii - Barros, H. P.; Valenti, Wagner Cotroni [UNESP] (Elsevier B.V., 2003)
The functional response between ingestion rate and food concentration was determined for each larval stage of Macrobrachium rosenbergii. Artemia franciscana nauplii were supplied at 2,4, 6, 8, 10 and 12 per milliliter. The nauplii were counted by sight using a Pasteur pipette and transferred to Petri dishes containing 40 ml of brackish water (12 parts per thousand) lying on the top of black plastic. One larva at each stage was individually placed into each Petri dish containing different food density. After 24 h, each larva was removed from the Petri dish and the leftover nauplii were counted. The amount consumed was determined by the difference between the initial and final number of nauplii. Ingestion rate (I) increased as food density (P) increased and was defined by the model I=I-m(1-e(-kP)). The results suggest four levels of ingestion during larval development. The first level includes stages II, III and IV, with average maximum consumption of about 40 nauplii/day; the second level includes stages V and VI, with consumption of approximately 55 nauplii/day; the third level includes stages VII and VIII, with consumption of 80-100 nauplii/day. The fourth level includes stages IX, X and XI, in which the high values for maximum ingestion (Im) exceed the load capacity of the medium. The low values for constant k (that may correspond to the adaptability of the food to prey characteristics, such as, size, mobility, etc.) obtained for stages IX, X and XI indicated that Artemia is not an adequate prey and there is necessity of a supplementary diet. The best relationship between predator and prey seemed to occur during stage IV Results obtained in the present work may subsidize future researches and serve as a guideline for practical considerations of feeding rates. (C) 2003 Elsevier B.V. B.V. All rights reserved.
Keywords: functional response; ingestion rate; prawn larvae; Macrobrachium; Artemia